2015
DOI: 10.1007/s13277-014-3028-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HOTAIR rs920778 polymorphism on breast cancer susceptibility and clinicopathologic features in a Turkish population

Abstract: Overexpression of Hox transcript antisense intergenic RNA (HOTAIR), a long non-coding RNA (lncRNA), is associated with cancer cell proliferation, invasion, progression, and metastasis as well as poor survival in a variety of human cancers including breast cancer (BC). A common functional single nucleotide polymorphism (SNP) rs920778 (T → C) in the intronic enhancer of the HOTAIR has been reported to influence HOTAIR expression and cancer predisposition, but the association of HOTAIR rs920778 polymorphism with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 29 publications
3
83
1
Order By: Relevance
“…Previous studies on the contribution of rs920778 to gastric cancer in a Turkish population [25] also showed no differences between patients and cancer-free controls; however, studies in other tumor types testing the importance of rs920778 or rs12826786 in the Chinese population have shown different allele frequencies between patients and cancer-free controls [22][23][24]. It was also showed previously that rs920778 variants do not influence gastric cancer susceptibility [25], whereas others have showed statistically significant associations between these SNPs and risk to develop gastric cardia adenocarcinoma [22], esophageal squamous cell carcinoma (ESCC) [23], breast cancer [26][27][28] or gastric cancer [24]. Such discrepancies might be attributed to the different genetic backgrounds of the studied populations, different sample sizes, and/or to the variety of tumor types analyzed.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies on the contribution of rs920778 to gastric cancer in a Turkish population [25] also showed no differences between patients and cancer-free controls; however, studies in other tumor types testing the importance of rs920778 or rs12826786 in the Chinese population have shown different allele frequencies between patients and cancer-free controls [22][23][24]. It was also showed previously that rs920778 variants do not influence gastric cancer susceptibility [25], whereas others have showed statistically significant associations between these SNPs and risk to develop gastric cardia adenocarcinoma [22], esophageal squamous cell carcinoma (ESCC) [23], breast cancer [26][27][28] or gastric cancer [24]. Such discrepancies might be attributed to the different genetic backgrounds of the studied populations, different sample sizes, and/or to the variety of tumor types analyzed.…”
Section: Discussionmentioning
confidence: 91%
“…Although HOTAIR expression has been reported as crucial in the carcinogenic process of many cancer types, and its abnormal expression was associated with patient poor prognosis, tumor grade, growth and invasion, and as a putative therapeutic target in glioma [19][20][21], few studies have focused on the significance of SNPs in HOTAIR affecting cancer risk [22][23][24][25][26][27][28]. Critically, no studies have evaluated the impact of HOTAIR SNPs in glioma risk and patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…reported that the HOTAIR SNP rs7958904 was associated with a low risk of colorectal cancer. Another SNP of HOTAIR, rs920778 (C>T), which increases the risk of developing several cancer types such as breast and gastric cancers [46,47], also appears to be linked to an increased risk for OC and poor prognosis [43]. These SNPs could be used as predictive tools for classifying individuals or populations susceptible to OC.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the immerse burden of breast cancer and challenges in its screening programs (2), determination of genetic factors which contribute to breast cancer risk among women is of value. In order to find their contribution in breast cancer risk, lncRNAs role in breast cancer has been evaluated in different studies with focus on their differential expression (3) as well as their variants at DNA sequence (4). Hox transcript antisense intergenic RNA (HOTAIR) is among lncRNAs with a defined role in regulation of cancer stem cell (CSC) plasticity and a possible target for anti-CSC treatments (1).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we investigated the association between three single nucleotide polymorphisms (SNPs) in HOTAIR gene (rs12826786, rs1899663 and rs4759314) and breast cancer risk in an Iranian population. The rational for selection of these SNPs was the observed association with breast cancer risk as well as patients' clinicopathological characteristics in other populations (4,13,14).…”
Section: Introductionmentioning
confidence: 99%